Perbandingan Sistem Pendidikan di Jepang dengan Indonesia - Sarmila Sarmila; Mislaini Mislaini; Liza Amelia (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
The education systems in Japan and Indonesia have significant differences in structure, philosophy and educational practices. Japan is known for its highly structured education system, high discipline, and an emphasis on academic excellence and hard work. The education system in Indonesia and in Japan has its own advantages and disadvantages. Currently, the education system in Indonesia needs more attention because it is ranked 72 out of 77 countries. In Indonesia, many educational experts have been born who are able to bring the education system in Indonesia to a better direction. One way to bring Indonesia's education system to a better direction is to compare it with a country with a good education system like Japan. In Japan, from the age of 0-4 years, children are more instilled with moral values, manners and discipline. When children in Japan have entered the 4th grade of elementary school, these children take exams that are not too burdensome for students at school. Indonesia can learn a lot with the education system in Japan.